2018
DOI: 10.1002/adsu.201800111
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Rechargeable Aqueous Zinc‐ and Aluminum‐Ion Battery Electrodes: Challenges and Outlook

Abstract: www.advsustainsys.comion-based chemistries exclusively. Though few reviews document electrode materials and their performances for rechargeable aqueous Zn-and Al-ion batteries, [23,[25][26][27] a comprehensive understanding of ion storage mechanisms remains poorly enunciated. We believe the key to successful implementation of MV-ion batteries requires a simultaneous understanding of various elemental chemistries, in context with each other. Here, we summarize reported electrochemical reactions for Zn-ion and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 202 publications
(428 reference statements)
1
157
0
1
Order By: Relevance
“…iii) Radius of Zn 2+ . Zn 2+ can tightly coordinate with water to form hydrated Zn 2+ ([Zn(H 2 O) 6 ] 2+ ), which inserted into the host cathode in different ways . When the ion‐channel size is not large enough to accommodate the hydrated Zn 2+ , desolvation could happen for the successful cation intercalation …”
Section: Energy Storage Mechanism Of Zibsmentioning
confidence: 99%
“…iii) Radius of Zn 2+ . Zn 2+ can tightly coordinate with water to form hydrated Zn 2+ ([Zn(H 2 O) 6 ] 2+ ), which inserted into the host cathode in different ways . When the ion‐channel size is not large enough to accommodate the hydrated Zn 2+ , desolvation could happen for the successful cation intercalation …”
Section: Energy Storage Mechanism Of Zibsmentioning
confidence: 99%
“…In tetragonal λ‐MnO 2 , Zn 2+ diffuses from 8a‐sites to neighboring 8a‐sites through 16c‐sites; however, Mn atoms at 16d‐sites (close to 16c‐sites) hinder the movement of Zn 2+ by electrostatic repulsion 81 . These findings confirm that further architecture modification is necessary for spinel‐type samples like λ‐MnO 2 and ZnMn 2 O 4 to become qualified Zn 2+ hosts considering their limited 3D tunnels and strong electrostatic repulsion toward Zn 2+ 26,38,39,48,67 . As shown in Figure 6, a treatment on the ZnMn 2 O 4 lattice was carried out to produce Mn vacancies or deficiencies by extracting oxygen anions, which lowers the electrostatic barrier for Zn 2+ transfer and alleviates the Mn species dissolution due to the higher Mn oxidation state.…”
Section: Crystal Structures Of Manganese Oxidesmentioning
confidence: 54%
“…The basic reason lies in the dissolution of Mn 2+ into the aqueous electrolyte, which leads to a change of stoichiometry and potential lattice rearrangement. Figure 3A shows the structure of an α‐MnO 2 , which has a 2 × 2 tunnel structure with corner‐sharing MnO 6 octahedra 34 . By comparing the XRD patterns of a Zn 2+ ‐intercalated α‐MnO 2 , Lee et al 43 found that the structure turned into a birnessite‐MnO 2 , which is similar with α‐MnO 2 except that the α‐MnO 2 layers are disconnected by one octahedral vacancy and are separated by two vertically aligned MnO 6 octahedra.…”
Section: Roles Of Water In Different Materialsmentioning
confidence: 99%